The variability of volatile organic compounds during a persistent fog-haze episode - Zhao, Yue; Lv, Jingjing; Zhou, Yue; An, Junlin; Zhu, Bin (Frontiers in Environmental Science, 2022)
A persistent fog-haze process associated with high pollution occurred in the northern suburbs of Nanjing from November to December 2013. Based on the comprehensive chemical and microphysical observations during the intense observation period, the composition characteristics, and variation rules of volatile organic compounds (VOCs) in the atmosphere under four weather conditions (slight haze, haze, fog, and dense fog) were compared and analyzed, the influencing factors of VOCs during extremely dense fog were discussed in more detail. The average concentrations of VOCs displayed as alkanes> aromatics> alkenes> alkynes, and the average concentrations of each VOCs component were ranked as dense fog> fog> haze> slight haze, the main factor contributing to the difference in concentrations of VOCs under different weather conditions is the boundary layer characteristics and photochemical reaction rate. Microphysical parameters such as liquid water content (LWC) were negatively correlated with VOCs concentration in dense fog (LWC>0.008 g·m-3). Also, the concentration of VOCs showed an oscillating decrease in extremely dense fog (LWC>0.12 g·m-3), and the total VOCs removal rate was close to 30%, which may be attributed to an indirect/direct removal effect, in which the enhanced collision and deposition of fog droplets promote the redistribution of VOCs gas-aqueous/particle partitioning, and remove them from the atmosphere by fog water.